ANALISIS KEMANDIRIAN KEUANGAN DAERAH KABUPATEN BANTUL TAHUN ANGGARAN 2016-2020 - Hafida (Jurnal Riset Daerah, 2022)
The goal of this study is to evaluate the Bantul Regency Government's level of financial independence for the fiscal years 2016–2020. Primary and secondary data sources are used in the descriptive qualitative methodology. Techniques for gathering data include interviews, observation, documentation, and literature reviews. Financial independence, financial reliance, effectiveness of regional original income, efficiency of regional original income, and revenue growth are the five ratios that are employed. The level of financial independence for the 2016–2020 Fiscal Year is still low, which means that influence from the federal government is still significant, according to the findings of the analysis utilizing ratios. The share of transfer income to income in Bantul Regency is still significant, at above 70%, at the level of regional financial dependency. However, both the effectiveness level and the efficiency level of regional original revenue are very high. Before the COVID-19 pandemic, the income growth rate was on the upswing.